Foundations of multinational financial management - Shapiro, Alan C. (Allyn and Bacon, 1994)
This work emphasizes concepts and practices, and features real-world examples that provide actual applications of financial concepts and theories, showing how the issues, tools and techniques of financial analysis and reasoning are being applied.